Generalized Derivations with Commutativity of Prime Rings - Jabel Atteya, Mehsin (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The main purpose of this paper is to study and investigate some results concerning generalized derivations (D,d) and (G,g) of prime ring R ,when the additive mapping acts as a left centralizer of R ,we obtain either d=0 or g=0,and when R contain a non –zero ideal U,R is commutative.